Alentejo Sustainable Tourism Observatory (ASTO): Scientific knowledge helping sustainable tourism implementation in real life - Borges, Maria do Rosário (2020)
The Alentejo Sustainable Tourism Observatory (ASTO) is a structure led by the University of Évora, that aims to measure and monitor tourism sustainability development in Alentejo territory. The goal is to develop a recognized UNWTO Sustainable Tourism Observatory, generating best practices that will be instrumental in improving evidence based decision making at the national, regional and local levels, in supporting the development of sustainable tourism and in the protection of the fragile natural resources that are the basis of tourism development. The implementation/ development of the ASTO constitutes the recognition of Sustainable Tourism as a vehicle to foster economic and social development, as well as potential source of negative social, cultural and environmental impacts, that have to be monitored and managed. Additionally, it is an opportunity to research and debate about global issues and the tourism sector, because it is one of the fastest-growing sectors worldwide, with various impacts that must be measured, monitored and managed. This means that knowledge production and sharing on tourism practices is an important issue on several scales (Borges, 2016; Borges et al, 2012) and common international methods for measuring tourism performance should be improved to strengthen destinations capacity to support innovative strategies and management process and promote more effective advantages to the civil society. The development of the Alentejo Sustainable Tourism Observatory (ASTO) maintains this important premise and goes further to produce and share knowledge concerning the following areas of tourism activities and within the specific context of sustainable tourism: employment, destination economic benefits, tourism seasonality, energy management, water management, waste water (sewage) management, solid waste management, local satisfaction with tourism and governance. In this context, ASTO is now trying to transform this information into knowledge, considering that empirical data needs to be compared with other realities (destinations). Given that, it is our intention to reflect and discuss the following questions: 1. What is the best process to adopt, so our research helps sustainable tourism development in the specific region Alentejo? 2. How to deal with the different existing methods for collecting data provided by official entities and other private tourism agents and energy providers.In the Alentejo region, some progress to implement sustainable indicators has been made by other initiatives.